Tsunami The Underrated Hazard - Bryant, Edward. (Springer International Publishing : Imprint: Springer, 2014)
It is a comprehensive and well illustrated textbook on all aspects of tsunami. I don't think there is any other book on the topic published. As one bookseller said after the Indian Ocean tsunami event, "I would have just filled my front window with copies and they would have walked out the store." This statement was just as relevant after the Japanese tsunami of 2011 and will be as relevant when the next large tsunami event happens, sooner rather than later. The book can be used by a student or layperson to gain encyclopedic knowledge about tsunami.